(untitled) (NAU Journal of Library and Information Science, 2022)
This paper sought to ascertain the involvement of academic women librarians in entrepreneurial skills acquisition for life after retirement in two selected academic libraries in Anambra State, Nigeria. Four research questions guided the study. This study adopted web-based survey research design using google form questionnaire as the instrument for data collection. The total population of this study was 27 academic women librarians from Prof. Festus Aghagbo Nwako Library in Nnamdi Azikiwe University, Awka and Federal Polytechnic Library, Oko all in Anambra State. The population was small and manageable hence the researchers adopted census enumeration technique to study the entire population. Instrument for data collection was web based structured questionnaire designed on four-point rating scale. A total of 27 copies of the questionnaire were distributed and all were returned. Data obtained from the respondents were analyzed using frequency counts, simple percentages, and mean(x) scores. The result of the analysis showed that academic women librarians identified the entrepreneurial skills available and its deployment for life after retirement. Based on the findings, the study recommended among other things that the management of the two institutions should encourage and introduce entrepreneurial skills acquisition to academic women librarians for post-retirement benefits.